Investigating the Development of the "Mobile Museum" from the Perspective of Service. (October 2016) - HUang, Chia‐Hui; Lin, Fang‐Suey
Abstract: During economic development, modern museums face competition from various leisure activities and entertainment sites, and to achieve sustainable development, museums should reflect on providing high‐quality service to satisfy visitors' expectations. Based on service design‐related theories, this research team conducted a case study to explore the planning, implementation, and meaning of Mobile Museums. It investigated design development from the perspective of public service design and summarized the policy, design, and service satisfaction results for Mobile Museums. Finally, the similarities in service processes are discussed between Mobile Museums and the general service industry. According to this study, attracting more visitors is the biggest issue facing museums today, as are the ways in which museums must actively provide service and become recognized to compete with others. This study identifies the onstage and backstage support of museums as well as their cultural features and non‐profit services.